Efektivitas Pengawasan Bawaslu Kota Kupang Terhadap Praktik Politik Uang Dalam Pemilihan Umum Legislatif Tahun 2024 - Faot, Kristin Valentin; Ratu Udju, Hernimus; Radji, Megi O (Artemis Law Journal, 2025)
The Election Supervisory Body (Bawaslu) is a body tasked with supervising the implementation of elections throughout the territory of the Republic of Indonesia. The number of Bawaslu members is 5 (five) people. One of the prevention and enforcement of violations supervised by Bawaslu is about money politics during the implementation of general elections. In the implementation of elections, money politics violations often occur, namely during the campaign period carried out by candidate candidates or campaign teams in order to gain votes and sympathy from the public. The type of research used in this study uses empirical legal research where this research method functions to see the law in a real sense and examine how the law works in the community. The results of the research and discussion refer to: (1) In the effectiveness of the supervision of the Kupang City Bawaslu against the practice of money politics in the 2024 legislative elections, it has been effective in this case, its supervision starts from prevention to action related to money politics issues. (2) The Kupang City Bawaslu faces obstacles in the form of weak resources and the public does not want to report money politics issues to the Bawaslu.